Attrition of undergraduate nursing students at selected South African universities - Erna Roos; Anna E. Fichardt; Margaret J. MacKenzie; Jacques Raubenheimer (Curationis, 2016)
Background: The nursing profession forms the backbone of many healthcare systems. It therefore needs a consistent supply of registered nurses to deliver continuous and safe quality healthcare, and to replace the nurses leaving or retiring from the profession. Attrition actively occurs among nursing students in South Africa and threatens the future supply of registered nurses. Aim: The aim of the study was to describe the attrition rate at selected South African universities and the factors influencing undergraduate nursing students to discontinue their nursing studies at these universities. Method: A quantitative descriptive design was followed. Heads of the nursing departments at the selected universities captured data with a specifically designed questionnaire. Thereafter their former nursing students provided information via a structured telephonic interview on the reasons why they discontinued the nursing programme. Results: The study revealed that attrition of undergraduate nursing students for three intake years (2007, 2008 and 2009) at the participating universities was between 39.3% and 58.7%. Academic and financial reasons as well as poor wellness and health were the main causes for attrition. Another factor was failure to cope with the demands of the clinical environment. Conclusion: Attrition might not occur immediately when a nursing student is challenged, as the student might exploit the various types of support offered. Although some nursing students do benefit from the offered support, a large number of nursing students still discontinue the undergraduate nursing programme.